2008
DOI: 10.1111/j.1749-4486.2008.01832.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and responsiveness of the medical research council dyspnoea scale to the presence and treatment of adult laryngotracheal stenosis

Abstract: Exertional dyspnoea is the hallmark symptom of laryngotracheal stenosis and for many patients it is the primary cause of disability. These findings confirm that the MRC dyspnoea scale is an appropriate outcome instrument for assessing dyspnoea associated with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 12 publications
2
33
0
3
Order By: Relevance
“…This finding is in agreement with other studies, which found that that dyspnea score is highly sensitive to the presence of varying degrees of laryngotracheal stenosis, and that there was only weak correlation between dyspnea score and spirometry variables. 8 Similar observations were found in COPD patients, in whom there is a strong correlation between dyspnea score and disability, but weaker correlations between dyspnea score and FEV 1 or peak expiratory flow. Impulse oscillometry may therefore be preferable for these patients, because of its better sensitivity and because patients with CAO may not be able to perform forced expiratory maneuvers.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This finding is in agreement with other studies, which found that that dyspnea score is highly sensitive to the presence of varying degrees of laryngotracheal stenosis, and that there was only weak correlation between dyspnea score and spirometry variables. 8 Similar observations were found in COPD patients, in whom there is a strong correlation between dyspnea score and disability, but weaker correlations between dyspnea score and FEV 1 or peak expiratory flow. Impulse oscillometry may therefore be preferable for these patients, because of its better sensitivity and because patients with CAO may not be able to perform forced expiratory maneuvers.…”
Section: Discussionsupporting
confidence: 68%
“…These include but are not limited to severe dyspnea, cough, fatigue, language barrier, cooperation, and cognitive impairment. Furthermore, in patients with CAO, flow-volume curves are characteristic when severe obstruction occurs, 8 and spirometry values may not correlate with the degree of airway narrowing. 9,10 Even when diagnostic for CAO, spirometry cannot localize the site of obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these indices target general dyspnea, 13,14 lower airwayrelated dyspnea (eg, asthma, Chronic Obstructive Pulmonary Disease, lung cancer), [15][16][17][18][19][20] or one component disorder of typical upper airway presentations in the voice clinic (eg, PVFMD in athletes, stenosis). 12,21 To date, there are no questionnaires that directly target the upper airway pathology population seen in an outpatient clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…10 Diagnostic methods related to upper airway dyspnea can still be patient-centered but need to be quantifiable to better understand the psycho-physiological and symptom severity impact upper airway breathing disorders have on the patient. 11,12 The use of instruments quantifying subjective patient perception in the clinical setting is not only vital to ensure patient-centered quality of care but also to comply with evidence-based medicine standards by documenting progress outcomes. 11 Disease-specific questionnaires have been proposed in the literature to help identify severity of symptoms in multiple disease processes.…”
Section: Introductionmentioning
confidence: 99%
“…Scales of dyspnea, like the Dyspnea Index [16] and quality of respiratory life in respiratory diseases have been validated for upper airway obstruction [17,18], but they are inadequate in emergency situations as can be conventional spirometry, therefore there where not performed in this case serie. No ABGs (arterial blood gases) have been performed before nor after control of the airway, because saturation and capnia often remain normal in case of even acute and severe laryngeal dyspnea; in this condition, hypoxemia and/or hypercarnia occur lately and abruptly.…”
Section: Discussionmentioning
confidence: 99%